Manejo y organizacion de post-cosecha, selecciones de color y calidad de grano, toma de rendimiento, almacenamiento, preparacion de la semilla para la siembra - López, E. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
The main activities involved in postharvest conservation and storage of beans are described, including determination of grain wt., MC, yield, color, and size. Seed storage should be conducte in the following conditions: 50-60 percent RH, 15-20 degrees C, and 12 percent MC in the grain stored in sacks and 7 percent MC in the grain stored in air-tight containers. Chemicals for seed conservation should be applied with care to avoid damage the embryo or to the seed germination power. (CIAT)